Technological Evaluation on Electronic System for Symmetry Induction - Ferreira, Camila Lisdalia Dantas (2018)
The present study aimed to develop a technological evaluation in the area of ​​assistive technologie to induce symmetry in the distribution of weight support between the feet, focusing on a patented Brazilian technology owned by the University of Brasília. A survey of scientific articles on the Web of Science data platform was carried out through keyword combinations, which resulted in 1,411 articles published between 2000 and 2016. A search for patents on the Questel Orbit Intelligence platform was also conducted through the combination between International Patent Classification (IPC) codes, Cooperative Patent Classifications (CPC) and keywords, which returned 235 patents published. The survey showed that Research and Development (R&D) activities in the area are under development and are concentrated in the United States and Europe. A SWOT Analysis was also conducted with the objective of strategically evaluating the technology.